Territorial Conflicts: Six Interpretations - Bobbio, Luigi (TeMA - Journal of Land Use, Mobility and Environment, 2011)
In contemporary societies, territorial conflicts, i.e. conflicts concerning unwelcome facilities or LULU (Locally Unwanted Land Use), tend to be more frequent and widespread than social conflicts. These conflicts are characterized by the protest of local communities that fight for the defence of their land from external aggressions, such as invasive artefacts (motorways, high speed lines, waste disposal plants, etc.) or human settlements (Roma camps, mosques, immigrants, etc.). This article aims to answer to three questions: 1) why these conflicts have increased in last decades? 2) what is their real stake? 3) how can be dealt with and with which possible outcomes? There is no single answer to these questions. If we take into consideration the discourses that are made on this issue, six types of narratives emerge that go in different directions. The territorial conflicts are seen, from time to time. (a) as the expression of particularistic and egoistic points of view that prevent the fulfilment of the general interest, (b) as the pressure of vested interests that exploit to the fear of the population for other purposes; (c ) as the consequence of the imbalance between concentrated costs and distributed benefits; (d) as a reaction to risks that are deemed unacceptable; (e) as the resistance of the places against the flows that invade or cross them; (f) as a demand for a different model of development. The conclusion is that such conflicts are multi-faceted phenomena. If we pay attention - as the current debate often do - only on one of these several dimensions, we risk to content ourselves with a simplified and, thereby, distorted interpretation.